A Legal-Normative Analysis of Marriage Registration in Indonesia from the Perspectives of Islamic Law and Positive Law, and Its Implications for the Legal Protection of the Family - Rosihah Rosihah; Abdul Raffi Ardiyanto; Fitria Adzuhri Mahyudin; Humaeroh Humaeroh (Journal of Human Interaction and Social Studies, 2026)
This study examines the legal status, normative foundations, and legal implications of marriage registration in Indonesia through the perspectives of Islamic law and positive law. The research employs a non empirical legal method based on a normative juridical approach and doctrinal legal analysis. Primary legal materials consist of Law Number 1 of 1974 concerning Marriage, Government Regulation Number 9 of 1975, and Law Number 16 of 2019, supported by scholarly literature on family law, legal pluralism, and sociolegal theory. The analysis explores the historical and regulatory development of marriage registration, the relationship between religious validity and state recognition, and the role of registration in securing legal protection for family members. The findings indicate that marriage registration functions as a legal mechanism that bridges Islamic legal principles and state legal authority within Indonesia’s plural legal system. Although classical Islamic jurisprudence does not generally classify registration as a substantive requirement of marriage validity, contemporary legal developments justify its necessity through the objectives of Islamic law and the demands of legal certainty. Registration strengthens the protection of rights relating to spouses, children, inheritance, maintenance, and access to judicial remedies. The study concludes that marriage registration constitutes an essential instrument for legal recognition, family welfare, and substantive justice in contemporary Indonesia.